RANCANGAN SEKTOR GROUND CONTROL PADA UNIT AERODROME CONTROL TOWER (TWR) DI PERUM LPPNPI CABANG SEMARANG - Muhammad Fahmi Umar; Sri Rahayu Surtiningtyas; Wisnu Darjono TU (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
This study aims to obtain an overview of the formation of the ground control sector in the Tower unit at Indonesian Air Navigation Service Provider Semarang Branch Office. The method used is a research and development method. The data analysis technique used is to use qualitative data analysis where the authors perform data reduction, data presentation and verification to produce a ground control sector design in the form of a tower cabin layout and the concept of operations followed by an expert or expert test. The study concludes that there is a problem in the Semarang Tower unit that is often the occurrence of load communication in the provision of flight traffic services caused by increased traffic, hourly movements that have exceeded runway capacity and complex airport layouts, it is necessary to open a new sector in the Tower unit, namely the ground control sector to reduce the delay due to load communication. In opening the ground control sector, it is necessary to develop an operational concept as a guideline in the operation, so that the activities of opening the ground control sector run clearly from shadow operation to full operation.